2004
DOI: 10.1167/iovs.04-0020
|View full text |Cite
|
Sign up to set email alerts
|

Severe Retinal Degeneration Associated with Disruption of Semaphorin 4A

Abstract: These findings identify a previously unknown function of Sema4A in the developing visual system and provide a useful model for understanding cell-cell interactions that occur between photoreceptors and the RPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…It is therefore possible that Sema4A also promotes growth cone collapse of cultured hippocampal neurons by stimulating R-Ras GAP activities through B-type plexins. Recent studies investigating the roles of semaphorins revealed not only the crucial involvements of each semaphorin in axon guidance but also in the ligand-receptor interactions between semaphorins and plexins essential for neural development (21)(22)(23)(24)(25). Plexin-B2 is not only a crucial component of neural tube development but also a key molecule that directs proliferation and migration of granule cell precursors in the developing dentate gyrus, olfactory bulb, and cerebellum (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore possible that Sema4A also promotes growth cone collapse of cultured hippocampal neurons by stimulating R-Ras GAP activities through B-type plexins. Recent studies investigating the roles of semaphorins revealed not only the crucial involvements of each semaphorin in axon guidance but also in the ligand-receptor interactions between semaphorins and plexins essential for neural development (21)(22)(23)(24)(25). Plexin-B2 is not only a crucial component of neural tube development but also a key molecule that directs proliferation and migration of granule cell precursors in the developing dentate gyrus, olfactory bulb, and cerebellum (21).…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that many semaphorins including Sema4D and Sema4A function in concert to regulate the migration of GnRH-1 cells in vivo. Analysis of Sema4A-deficient mice revealed the non-redundant roles of Sema4A in the developmental path of retinal photoreceptor cells, although the receptors involved have not yet been clarified (25). For these reasons, Sema4A may play a crucial role in the development of the neural system through the interaction with B-type plexins in concert with other semaphorin members.…”
Section: Discussionmentioning
confidence: 99%
“…In the P10 cornea we detected expression of Sema4a and Nrp1, encoding semaphorin 4A and neuropilin, respectively. Semaphorin 4A has been studied in the retina (Rice et al 2004) with no prior reports of its presence in the cornea. Semaphorin 3A and its receptor neuropilin have been reported to play a role in the initial formation of a nerve ring surrounding the cornea (Lwigale and Bronner-Fraser 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Most genes associated with autosomal dominant forms of RP are expressed specifically in rod photoreceptors, including genes associated with phototransduction (RHO, GUCA1B) (33,34), photoreceptor-specific transcription factors (CRX, NRL) (35,36), or structural characteristics specific to photoreceptors (RDS, RP1) (37)(38)(39)(40). Other autosomal dominant RP genes are expressed in heterogeneous tissues including the retina and/or the retinal pigment epithelium, such as pre-mRNA splicing factors PRPF3, PRPF8, and PRPF31 (41-43) and the transmembrane protein SEMA4A (44). RP17 is associated with the R14W missense mutation in the signal sequence of CA4 (11).…”
Section: Discussionmentioning
confidence: 99%